The Story of Bagumbayan and the Emerging Filipino and Identity - Padilla, Efren N. (Silliman Journal, 2022)
This paper asks a simple question: Does the traditional understanding of the Filipino story possess the imagination to help us face the callenges of the new millenium? In order to answer this question, this essay will examine the prospect of the contemporary Filipino story against the story of Bagumbayan. This Filipino word come from the phrase Bagong Bayan which leterall means "New Country" or 'New Town'. As a metaphor for our own story as a people, it can be interpreted in two ways: One is the road to Bagumbayan which represents the nationalistic story and is the fulfillment of our yearning to be an independent nation-state. The other is the road from Bagumbayan which represents the diasporic story, the current scattering of Filipinos all over the world. This paper arues that the latter now supplies us both with the language and discourse of who we are, how we see ourselfves, how we reproduce our communities, how we reclaim ourselfves, and how we reconstruct our communities. In short, how we live.